E-Arusun: Pengembangan Aplikasi Untuk Manajemen Data Administrasi Rumah Susun Berbasis Web Menggunakan Metodologi Prototype - Wina Firly, Tiara; Ayumi, Vina (JSAI (Journal Scientific and Applied Informatics), 2024)
Managing apartment buildings is a critical aspect of property management, encompassing leasing, resident administration, facility maintenance, and complaint handling. Manual management often faces various challenges, such as inefficient data organization, slow responses to complaints, and a lack of operational transparency. This study aims to develop E-Arusun with a focus on Rumah Susun Sewa (Rusunawa) KS. Tubun Jakarta as the research object. The application utilizes the prototype methodology, starting from the requirements gathering phase, prototype development, evaluation, coding, and system testing. E-Arusun was developed using PHP as the server-side programming language and HTML and CSS for the user interface. The system is designed to address various challenges in managing apartment buildings by providing key features such as register, login, user management, apartment management, kiosk management, rental transaction management, and complaint management. Additionally, tenants can utilize features such as viewing bills, submitting complaints, and monitoring payment status